National Security Challenges and the Quest for True Federalism in Nigeria: the Issue of Amotekun (South-West Regional Security Network) - Oluro, Mayowa; Oluwasuji, Clement (Advances in Social Sciences Research Journal, 2021)
Among the various challenges that the Nigerian State has had to contend with since its inception, incessant security challenges stand out. Indeed, these challenges have continued to defy the various strategies put in place to check them by various federal security agencies in the country, including the Military, Police, Road Safety, Civil Defense, Immigration, and Custom, thereby rendering them ineffective and inefficient, and as such contributing to louder calls for restructuring of the country. State Governors in the South-West in response to the security challenges facing the region formed the Western Nigerian Security Network (WNSN) code-named Operation Amotekun, the Yoruba name for Leopard, a wild animal known for its great agility and hunting prowess. This paper seeks to examine, 1. The current federal structure vis-à-vis the various security challenges in the country, 2. The formation of the Western Nigerian Security Network (Amotekun), i.e., its prospects, likely challenges and mode of operation, and 3. Propose some policy options to aid the performance and efficiency of Amotekun and any other that may follow.